(untitled) (Research, Society and Development, 2021)
Objective: To verify the literature on pelvic floor disorders caused by radiotherapy after the treatment of cervical cancer. Methods: An integrative literature review, in which bibliographies published in Pubmed, Scielo, Portal Capes, Lilacs, Cochrane, PEDro and Medline databases were checked, from 2010 to 2021. The keywords used were “dysfunctions”, “pelvic floor”, “radiotherapy” and “neoplasms of the cervix” and their correlates in English and Spanish. Results: At the end of the analysis, seven studies were included for meeting the research criteria, in which it was found that the most reported pelvic dysfunctions in the literature after radiotherapy for the treatment of cervical cancer are dyspareunia and urinary incontinence. Final considerations: It was possible to infer that this type of intervention has numerous impacts on the pelvic floor, especially urinary incontinence and dyspareunia. It suggests the broader insertion of recovery activities through physiotherapy for changes resulting from this type of treatment, aiming at improving the functionality of the pelvic floor muscles and reducing pelvic changes, which bring complications to physical and psychological well-being of this population.